Mortality, hospitalizations, and expenditures for the Medicare population age 65 and older, 1999–2013 - Krumholz, Harlan M. (JAMA, 2015)
IMPORTANCE: In a period of dynamic change in health care technology, delivery and behaviors, tracking trends in health and health care can provide a perspective on what is being achieved. OBJECTIVE: To comprehensively describe national trends in mortality, hospitalizations, and expenditures in the Medicare Fee-For-Service population between 1999 and 2013. DESIGN, SETTING, AND PARTICIPANTS: Serial cross-sectional analysis of Medicare beneficiaries aged ≥65 years between 1999 and 2013 using Medicare denominator and inpatient files. MAIN OUTCOMES AND MEASURES: For all Medicare beneficiaries, trends in all-cause mortality; for Fee-for-Service beneficiaries, trends in all-cause hospitalization and hospitalization-associated outcomes and expenditures. Also, geographic variation, stratified by key demographic groups, and changes in the intensity of care for Fee-For-Service beneficiaries in the last 1, 3, and 6 months of life. RESULTS: The sample consisted of 68,374,904 unique Medicare beneficiaries (Fee-For Service and Medicare Advantage). All-cause mortality for all Medicare beneficiaries declined from 5.30% in 1999 to 4.45% in 2013 (difference, 0.85 percentage points; 95% confidence interval [CI], 0.83 to 0.87). Among Fee-for-Service beneficiaries (n=60,056,069), the total number of hospitalizations per 100,000 person-years decreased from 35,274 to 26,930 (difference, 8,344; 95% CI, 8,315 to 8,374). Mean inflation-adjusted inpatient expenditures per Medicare Fee-for-Service beneficiary declined from $3,290 to $2,801 (difference, $489; 95% CI, 487 to 490). Among Fee-for-Service beneficiaries in the last 6 months of life, the number of hospitalizations decreased from 131.1 to 102.9 per 100 deaths (difference 28.2; 95% CI, 27.9 to 28.4), the percentage of beneficiaries with one or more hospitalizations decreased from 70.5 to 56.8 per 100 deaths (difference 13.7; 95% CI, 13.5 to 13.8); while the inflation-adjusted inpatient expenditure per death increased from $15,312 in 1999 to $17,423 in 2009 and then decreased to $13,338 in 2013. Findings were consistent across geographic and demographic groups. CONCLUSIONS AND RELEVANCE: Among Medicare Fee-for-Service beneficiaries aged ≥65, all-cause mortality rates, hospitalization rates, and expenditures per beneficiary decreased from 1999 to 2013. In the last 6 months of life, total hospitalizations decreased and inpatient expenditures decreased in recent years.